PENGARUH KEPUASAN KERJA, KOMITMEN ORGANISASIONAL, MOTIVASI TERHADAP KINERJA MELALUI ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA KARYAWAN SPBU 4452212 BREBES - Muklis Ali Sobirin; Mr. Maufur (Program Studi Magister Manajemen, Universitas Pancasakti Tegal - Indonesia, 2017)
The purpose of this research to 1 ) analyze the influence of motivation of the performance of officers from Tegal city 2 ) analyze the influence of discipline work on performance officers from Tegal city 3 ) analyze the influence of motivation and discipline work on performance officers from Tegal .Respondents in this research as many as 84 people .These respondents is officers from tegal city .The necessary data collected to technique the questionnaire , literature study , observation and interview .Data analysis used in this research was descriptive analysis , test the assumption classical , regression analysis multiple , the testing of hypotheses and analysis the coefficients determination .The research can be concluded that is the positive and significant motivation to the performance of officers from tegal city . This is evidenced from the test hypothesis in partial obtained value significance of 0,011 which is smaller than 0.05 .The results of research suggests that is the positive and significant discipline work of the performance of the officers from tegal city .This is evidenced from the test hypothesis in partial obtained value significance of 0,000 which is smaller than 0.05 .The results of research suggests that is the positive and significant of the incentives and discipline work together to the performance of officers from tegal city .This is evidenced from the test hypothesis simultaneously obtained value significance ( test anova f ) of 0,000 which is smaller than 0.05 . Keyword: motivation, discipline, performance